Diversity and Palynology of Araceous Plants on Limestone Mountains in Lop Buri and Saraburi Provinces, Thailand - Maneeanakekul, Sutida; Sookchaloem, Duangchai (วารสารเกษตร มสธ. (Online), 2020)
A study on diversity and palynology of Araceous plants in Lop Buri and Saraburi provinces, Thailand was carried out between February 2011 and December 2017. The purposes of this study are to report on species diversity and to investigate the morphological characteristics and pollen characteristics of some plants with threatened status. Fifty-five specimens were collected from various limestone areas in Lop Buri and Saraburi provinces. Twenty species were identified i.e. Aglaonema cochinchinense, A. simplex, Alocasia acuminata, Amorphophallus paeoniifolius, A. albispathus, A. saraburensis, A. lacourii, Cryptocoryne crispatula var. balansae, Hapaline kerri, Lasia spinosa, Pothos scandens, Pycnospatha arietina, Rhaphidophora peepla, Scindapsus sp., Typhonium laoticum, T. orbifolium, T. saraburiense, T. trilobatum, T. supraneeae and T. muaklekense. Five species are new locality records. The pollen characteristics of 14 species were investigated using a scanning electron microscope (SEM) technique. Most pollen grains were inaperture (except Pothos scandens and Pycnospatha arietina: monosulcate aperture). The polar axis diameter and equatorial axis diameter of pollen grains were 18-60 µm and 11-50 µm, respectively. Four pollen shapes were identified: oblate spheroidal, spheroidal, subprolate, and prolate. Exine sculpturings were perforate, psilate, striate, spinose, areolate and reticulate. Pothos scandens, Pycnospatha arietina, Alocasia acuminata, Aglaonema simplex, A. cochinchinense, Hapaline kerrii, T. saraburiense, T. orbifolium, T. laoticum and T. muaklekense were newly examined. A key to species was provided based on morphological characters and pollen features (shape and sculpturing).